Improving Community Durability During the Covid-19 Pandemic in the Development of Tourism Based on Local Wisdom in the Traditional Village of Krebelahan - I Nyoman Gede Sugiartha; A.A. Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2022)
Each lecturer is encouraged to package community service activities in groups and as individuals, which will later show concern for the community. As a higher education institution, Warmadewa University must always adhere to the Tridharma of Higher Education in accordance with the predetermined vision and mission. The aims of this research are as a form of the Lecturer's dedication to the community, to provide opportunities for Lecturers to direct service with partnerships to the target object in Banjar Krembahan Kab. Karangasem Implements one of the Tri Dharma of Higher Education in terms of Service and improving cooperative relations between universities and the community. The implementation method carried out in the community service program is by Program to increase public awareness of environmental conservation and environmental preservation program and A sustainable partnership for environmental conservation in Banjar Krembahan Kab. Karangasem. The result shows increase community resilience to the effects of the COVID-19 pandemic is to increase foreign tourist visits and increase people's income in Banjar Krelahan. The things that should be done in the Banjar Krembahan Tourism Area, Kubu District, Karangasem Regency, there is a need for public awareness about the importance of maintaining community resilience from the effects of the COVID-19 pandemic, so there is a need for public awareness about the importance of the environment not being maintained in a sustainable manner. As well as providing input on the influence of community resilience against the COVID-19 pandemic in the Krelahan, Kubu tourist area and the public awareness needs to be given a sense of binding.